PENERAPAN METODE CASE BASED REASONING UNTUK MENDIAGNOSA PENYAKIT PADA BURUNG LOVERBIRD - Vivi Elvina Simanjutak; Labuan Nababan; Fina Nasari (STMIK Pontianak, 2018)
The Expert System is one part of Artificial Intelligence that contains the knowledge and experience inserted by many experts into a particular area of knowledge, so that everyone can use it to solve specific problems, in this case the diagnosis of the disease in lovebird birds. Bird lovebird is one type of grain-eating birds. The colors, sounds and funny behavior make lovebird birds one of the options as a pet. But lovebirds are also susceptible to disease. By utilizing the Case Based Reasoning method, an application can be generated to diagnose lovebird bird disease. With the hope that this system can be used as a means or as a knowledge in maintaining the health of lovebird birds and help you to get optimal results in maintaining the growth of each lovebird bird. The Case Based Reasoning Method (CBR) is used in the Lovebird Bird Disease Diagnostic application using Nearest Neighbor Calculations, where new case data will be compared against the old case data in the database, and then calculated the similarity criteria based on the formula or the applicable terms.Kata kunci: Sistem Pakar, Lovebird Bird, Diagnosis, Case Based Reasoning.